Mesenchymal Stem Cell Therapy for Ischemic Stroke in Animal Model: A Systematic Review - Muhammad Agus Aulia; Keri Lestari; Ahmad Faried; Cynthia Retna Sartika; Andi Wijaya; Achmad Adam; Hanna Gunawan; Rima Haifa; Nabilla Farah Naura; Billy Yosua Costantin Pongajow (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Stroke is one of many leading causes of death and disability worldwide. Despite decades of research, treatment for stroke recovery is still inadequate. Recently, mesenchymal stem cell (MSC) therapy is considered as one of the potential treatments for stroke due to their capabilities to repair or regenerate damaged tissues, as well as immunomodulators in inflammatory conditions. Many pre-clinical and clinical trials have shown MSC therapy feasibility, safety, and efficacy in treating stroke. However, evidence regarding the optimal treatment plan and factors that can improve stem cell functional outcomes in treating stroke needs to be further explored. Therefore, a systematic review was conducted.METHODS: Recent literatures from 2015-2022 regarding stem cell therapies, specifically MSC on ischemic stroke, were collected from two reliable databases: PubMed and PubMed Central. Collected literatures were properly applied to inclusion-exclusion criteria and appraised critically. Keyword strategies on databases were employed, including both medical subject headings (MeSH).RESULTS: Five literatures from 726 were identified and used for systematic review. All animal model in the literatures were prepared to have middle cerebral artery occlusion. All studies indicated that MSC therapy is a safe and reliable procedure despite the variety of transplantation routes. No report of toxicity, rejection reaction, nor infection on MSC treated groups.CONCLUSION: Stem cell sources, dosages, and delivery routes could be resourceful for future translational studies to ensure the safety and efficacy of MSC therapy for ischemic stroke.KEYWORDS: ischemic stroke, mesenchymal stem cells, regenerative medicine, immunomodulator